A New Multichelating Acid System for High-Temperature Sandstone Reservoirs - Nianyin Li; Qian Zhang; Yongqing Wang; Pingli Liu; Liqiang Zhao (Journal of Chemistry)
Sandstone reservoir acidizing is a complex and heterogeneous acid-rock reaction process. If improper acid treatment is implemented, further damage can be induced instead of removing the initial plug, particularly in high-temperature sandstone reservoirs. An efficient acid system is the key to successful acid treatment. High-temperature sandstone treatment with conventional mud acid system faces problems including high acid-rock reaction rate, short acid effective distance, susceptibility to secondary damage, and serious corrosion to pipelines. In this paper, a new multichelating acid system has been developed to overcome these shortcomings. The acid system is composed of ternary weak acid, organic phosphonic chelating agent, anionic polycarboxylic acid chelating dispersant, fluoride, and other assisted additives. Hydrogen ion slowly released by multistage ionization in ternary weak acid and organic phosphonic within the system decreases the concentration of HF to achieve retardation. Chelating agent and chelating dispersant within the system inhibited anodic and cathodic reaction, respectively, to protect the metal from corrosion, while chelating dispersant has great chelating ability on iron ions, restricting the depolarization reaction of ferric ion and metal. The synergic effect of chelating agent and chelating dispersant removes sulfate scale precipitation and inhibits or decreases potential precipitation such as CaF2, silica gel, and fluosilicate. Mechanisms of retardation, corrosion-inhibition, and scale-removing features have been discussed and evaluated with laboratory tests. Test results indicate that this novel acid system has good overall performance, addressing the technical problems and improving the acidizing effect as well for high-temperature sandstone.